2009
DOI: 10.1111/j.1748-1716.2009.01970.x
|View full text |Cite
|
Sign up to set email alerts
|

AMP‐activated protein kinase in the regulation of hepatic energy metabolism: from physiology to therapeutic perspectives

Abstract: As the liver is central in the maintenance of glucose homeostasis and energy storage, knowledge of the physiology as well as physiopathology of hepatic energy metabolism is a prerequisite to our understanding of whole-body metabolism. Hepatic fuel metabolism changes considerably depending on physiological circumstances (fed vs. fasted state). In consequence, hepatic carbohydrate, lipid and protein synthesis/utilization are tightly regulated according to needs. Fatty liver and hepatic insulin resistance (both f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
377
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 444 publications
(395 citation statements)
references
References 140 publications
15
377
0
3
Order By: Relevance
“…The adenosine monophosphate analogue 5-aminoimidazole-4-carboxamide ribonucleotide (AICAR) activates AMPdependent protein kinase (AMPK), which is a key regulator of energy metabolism and thus a potential target for treatment of obesity-related complications [4,5]. Evidence from experimental models has shown that AICAR may attenuate metabolic [6][7][8], hepatic [9][10][11] and renal pathophysiology [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The adenosine monophosphate analogue 5-aminoimidazole-4-carboxamide ribonucleotide (AICAR) activates AMPdependent protein kinase (AMPK), which is a key regulator of energy metabolism and thus a potential target for treatment of obesity-related complications [4,5]. Evidence from experimental models has shown that AICAR may attenuate metabolic [6][7][8], hepatic [9][10][11] and renal pathophysiology [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…AMPK has been identified as a master regulator of cellular energy status and plays a crucial role against energy‐restricted conditions 22. Among them, the glucose deprivation is one of the most important factors to regulate the AMPK activity 23.…”
Section: Discussionmentioning
confidence: 99%
“…In human adipocytes, b-adrenergic stimulation of lipolysis was found to be down-regulated by concomitant activation of AMPK through TZDs (Bourron et al 2010). Overall, acute AMPK activation in adipose tissue leads to an inhibition of both lipogenesis and lipolysis, whereas it increases fatty acid oxidation and glucose transport (Viollet et al 2009;Daval et al 2006). It seems counter-intuitive (Daval et al 2006) that AMPK inhibits lipolysis, although it is itself activated in situations of increased lipolysis.…”
Section: Ampk Function In Adipose Tissuementioning
confidence: 97%
“…Muscle AMPK is involved in the coordinated transcription of genes important for lipid and glucose metabolism during exercise and for acute control of metabolic fluxes, namely the switch from carbohydrate to lipid oxidation (Hardie 2008;Zhang et al 2009;McGee and Hargreaves 2010;Canto et al 2010;Viollet et al 2009). Thus, AMPK is activated by muscle contraction, which depletes ATP leading to an increase in the AMP/ATP ratio.…”
Section: Ampk Function In Smmentioning
confidence: 99%